Perbandingan Premi Asuransi Jiwa pada Saat Akhir Tahun Kematian dan pada Saat Kematian - Mugnii Mukhlis, Aisyah; Lowisa Br Purba, Dewi; Adella, Nagita (VISA: Journal of Vision and Ideas, 2024)
Life insurance is a promise from the insurance company (insurer) to its customer (insured) that if the customer experiences the risk of death in their life, the insurance company will provide compensation. The amount of money paid by the insured to the insurer, the amount of which has been determined, is called the premium. The premium paid by the policy holder (insured) will be allocated by the insurance company for compensation or benefits which will be returned to the insured. In this study, simulated data was used to see the comparison of life insurance premiums at the end of the year of death and at the time of death. The results of this study conclude that the premium value of insurance compensation payments at the end of the year of death is smaller than the premium value of insurance compensation payments at the time of death.